A dual-modal molecular probe for near-infrared fluorescence and photoacoustic imaging of peroxynitrite - Zhang, Jianjian (2020)
Peroxynitrite (ONOO-), a reactive and short-lived biological oxidant, is closely related with many pathological conditions such as cancer. However, real-time in vivo imaging of ONOO- in tumors remains to be challenging. Herein, we develop a near-infrared fluorescence (NIRF) and photoacoustic dual-modal molecular probe (CySO3CF3) composed of a water-soluble hemicyanine dye caged with a trifluoromethyl ketone moiety for in vivo imaging of ONOO-. The trifluoromethyl ketone moiety can undergo a series of ONOO--induced cascade oxidation-elimination reactions, leading to sensitive and specific fluorescence and photoacoustic turn-on responses toward ONOO-; whereas, a zwitterionic structure of the hemicyanine component ensures good water-solubility. Thus, CySO3CF3 not only specifically detects ONOO- in solution and cells with the limit of detection down to 53 nM but also allows for NIRF and photoacoustic dual-modal imaging of ONOO- in the tumors of living mice.